L'intégration des changements climatiques dans les politiques publiques locales : Le cas du golfe du Morbihan - Betty Queffelec (VertigO)
First climate change effects, especially in the coastal zone, stress the adoption of a long term strategy at all decision levels. Even if disruptions are unavoidable, there are still doubts concerning their extent and local effects. They will partly depend on our reaction capacities, especially concerning the mitigation of greenhouse gas emissions. Even quite recently perceived as distant and hypothetical, gradually the phenomenon is beginning to take shape. The increasing concern of local collectivities is stressed by its context: international (United Nations Framework Convention on Climate Change and Kyoto Protocol), european (climate energy package) and national (Grenelle de l'environnement). In France, their willingness of action can become concrete through a specific tool, the territorial climate plan. But, the cross-cutting feature of the subject overflows this framework. The Bretagne region strongly integrate climatic concern especially in the Morbihan gulf regional natural parc project and in its energy plan.